2001
DOI: 10.1097/00006454-200104000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in human immunodeficiency virus type 1-infected and uninfected children in Nairobi

Abstract: Normal lymphocyte subset values among African children differ from those in other populations. Significant differences are detectable by 3 months of age in CD4+ and CD8+ lymphocyte percentages among perinatally infected infants, which may be useful as an adjunct in diagnosis. Transient differences observed among HIV-1-exposed but uninfected infants could reflect a successful immune response to HIV-1 challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 20 publications
7
50
1
Order By: Relevance
“…As variously reported for healthy Ugandan, 16 Tanzanian, 17 Kenyan, 18 and Gambian 19 children, we also found that RBC indices (RBC count, Hb, and Ht) increased and WBC count decreased with age in healthy Malian children. Children in all three age groups (3-5, 6-8, and 9-12 years) also showed increased RBC indices and decreased WBC counts as they aged through a single 7-month transmission season, irrespective of whether they experienced one or more episodes of malaria or carried malaria-protective RBC polymorphisms.…”
Section: Discussionsupporting
confidence: 89%
“…As variously reported for healthy Ugandan, 16 Tanzanian, 17 Kenyan, 18 and Gambian 19 children, we also found that RBC indices (RBC count, Hb, and Ht) increased and WBC count decreased with age in healthy Malian children. Children in all three age groups (3-5, 6-8, and 9-12 years) also showed increased RBC indices and decreased WBC counts as they aged through a single 7-month transmission season, irrespective of whether they experienced one or more episodes of malaria or carried malaria-protective RBC polymorphisms.…”
Section: Discussionsupporting
confidence: 89%
“…HIV-1 sequence diversity was assessed by examining the predominant proviral DNA sequence in two wellcharacterized HIV-infected cohorts, composed of female commercial sex workers (13,14) and women seeking antenatal care (5,12), located in Nairobi, Kenya. A total of 240 HIV-positive women were randomly selected based on sample availability for inclusion in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 215 HIV-positive women enrolled in a welldescribed cohort of commercial sex workers with high exposure to HIV in the Pumwani area of Nairobi, Kenya, were randomly selected based on sample availability (13,14). An additional 25 HIV-positive women from a perinatal transmission cohort of similar socioeconomic status and ethnicity but with low exposure to HIV were similarly selected (5,12). All women are believed to be infected with HIV by heterosexual contact, and all were antiretroviral naive at the time of the study.…”
Section: Methodsmentioning
confidence: 99%
“…These data closely agree with information from outside experts and with published data on the subject. 16,25,26,28 Benefits to high-risk children According to data from South Africa, HIV-related mortality among HIVexposed infants peaks at 2 to 3 months postpartum. 29 By training health-care staff to apply the modified clinical criteria and rapid HIV antibody test, more children at high risk of dying can be identified and treated.…”
Section: Discussionmentioning
confidence: 99%
“…This translates into a specificity of 99% for CD4 count in our model. 25,26 The 1% of HIV uninfected infants whose CD4 count is below WHO thresholds …”
Section: Sensitivity and Specificity Of Cd4 Cell Countmentioning
confidence: 99%